Mechanisms and Regulation of DNA-Protein Crosslink Repair During DNA Replication by SPRTN Protease - Perry, Megan; Ghosal, Gargi (Frontiers in Molecular Biosciences, 2022)
DNA-protein crosslinks (DPCs) are deleterious DNA lesions that occur when proteins are covalently crosslinked to the DNA by the action of variety of agents like reactive oxygen species, aldehydes and metabolites, radiation, and chemotherapeutic drugs. Unrepaired DPCs are blockades to all DNA metabolic processes. Specifically, during DNA replication, replication forks stall at DPCs and are vulnerable to fork collapse, causing DNA breakage leading to genome instability and cancer. Replication-coupled DPC repair involves DPC degradation by proteases such as SPRTN or the proteasome and the subsequent removal of DNA-peptide adducts by nucleases and canonical DNA repair pathways. SPRTN is a DNA-dependent metalloprotease that cleaves DPC substrates in a sequence-independent manner and is also required for translesion DNA synthesis following DPC degradation. Biallelic mutations in SPRTN cause Ruijs-Aalfs (RJALS) syndrome, characterized by hepatocellular carcinoma and segmental progeria, indicating the critical role for SPRTN and DPC repair pathway in genome maintenance. In this review, we will discuss the mechanism of replication-coupled DPC repair, regulation of SPRTN function and its implications in human disease and cancer.